Study of corrosion inhibition performance of Glutaraldehyde on Aluminium in nitric acid solution - Husainia, Musa; Usmana, Bishir; Ibrahim, Muhammad Bashir (University of Eloued جامعة الوادي, 2019)
The inhibition effect of glutaraldehyde on the corrosion behavior of aluminium in 1.4 M nitric acid solution was studied using weight loss method, adsorption studies and characterized instrumentally by Fourier Transform Infrared Spectroscopic (FT-IR) analysis. The effects of inhibitor concentration, temperature and surface coverage were all investigated. The effect of inhibitor concentration and other parameters were evaluated for different inhibitor concentrations and the probable mechanism for the studied inhibitor was also proposed. The results showed that glutaraldehyde possess an excellent inhibiting effect toward the corrosion of aluminium in nitric acid solution with highest inhibition efficiency of 84.68, 81.34 and 76.87 % at 308, 313 and 318 K in the presence of 0.1 M inhibitor concentration. The values of the activation energy, rate constant, half-life and rate constant in uninhibited acid solution were 31.84 kj mol-1 , 3.9 k ×10-3 hr-1 and 1.76 × 102 hr which changed to 57.64 kj mol-1 , 0.60 k ×10-3 hr-1 and 11.55 hr in the presence of 0.1 M inhibitor concentration. The positive values of enthalpy reflect the endothermic nature of the reaction. The negative values of entropy (ΔS) signified that the activated complex in the rate determining step represented an association, rather than dissociation. The adsorption of the inhibitor on the metal surface followed Langmuir adsorption isotherm.
Artical
Keywords: Corrosion; Glutaraldehyde; Nitric Acid; FT-IR; Kinetic; Thermodynamic parameters